PHARMACY STUDENTS’ LISTENING COMPREHENSION: PROBLEMS AND STRATEGIES - Risa Arroyyani (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2021)
This study is aimed to find out students’ listening problems and listening strategies. The research type is qualitative research using questionnaires and interviews as the instruments. Descriptive statistics were used to analyze data obtained from the questionnaires, and interpretation of coding to analyze data from the interview script. The respondents were 31 pharmacy students involved in English for Pharmacy class and three of them were involved in a structured interview session.